Megadrought in the Carolinas : The Archaeology of Mississippian Collapse, Abandonment, and Coalescence - Cable, John S. (Book collections on Project MUSE., 2019)
"An enigma in southeastern archaeology is why a vast swath of land in coastal central South Carolina was abandoned in the 1400s. By 1540 and the Spanish Entrada of De Soto, this area was called the Desert of Ocute, after the Ocute people. Cable's long-term research shows that abandonment took place because of prolonged drought, in fact a megdraought, as there was elsewhere from Chaco Canyon to Cahokia in earlier centuries. This book considers the implications of the displacement of the Ocute into the surrounding settlements. Cable suggests that these immigrants experienced regional hostility and that new cultural groups formed that began to replace the old social structure of chiefdoms and platform mounds. Confederated societies emerged that had a much wider geographic reach. Crowding into the sustainable river valleys of the Piedmont and Mountain zones necessitated technological and social adaptations for an intensification of agriculture. Cable surmises that if European contact had been delayed several hundred years, these peoples would have developed as per the complex Cahokians"--